2009
DOI: 10.1128/mcb.01836-08
|View full text |Cite
|
Sign up to set email alerts
|

The NF90-NF45 Complex Functions as a Negative Regulator in the MicroRNA Processing Pathway

Abstract: The positive regulatory machinery in the microRNA (miRNA) processing pathway is relatively well characterized, but negative regulation of the pathway is largely unknown. Here we show that a complex of nuclear factor 90 (NF90) and NF45 proteins functions as a negative regulator in miRNA biogenesis. Primary miRNA (pri-miRNA) processing into precursor miRNA (pre-miRNA) was inhibited by overexpression of the NF90 and NF45 proteins, and considerable amounts of pri-miRNAs accumulated in cells coexpressing NF90 and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
193
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(202 citation statements)
references
References 60 publications
7
193
1
1
Order By: Relevance
“…In addition to regulating the expression of different genes post-transcriptionally, NF90 also takes part in miRNA biogenesis. As a competitor for the association of the microprocessor complex with pri-miRNAs, NF90 usually inhibits miRNA production (27,41,42). We found that lncRNA-LET depletion resulted in elevated level of NF90 which in turn blocks miR-145 biogenesis by competitively binding to pri-miR-145 specifically.…”
Section: Discussionmentioning
confidence: 78%
“…In addition to regulating the expression of different genes post-transcriptionally, NF90 also takes part in miRNA biogenesis. As a competitor for the association of the microprocessor complex with pri-miRNAs, NF90 usually inhibits miRNA production (27,41,42). We found that lncRNA-LET depletion resulted in elevated level of NF90 which in turn blocks miR-145 biogenesis by competitively binding to pri-miR-145 specifically.…”
Section: Discussionmentioning
confidence: 78%
“…The overlapping components between epitope-tagged Drosha (38) and TDP-43 (in this study) strongly suggest that TDP-43 is involved in microRNA biogenesis. Indeed, NF45/NF90 has been shown to complex with pre-miRNAs, and this association reduces the generation of mature miRNAs (49). In addition, adenosine deaminases (ADARs), found to bind to TDP-43 in our proteomic study, are known to influence microRNA processing through their editing activities (50).…”
Section: Discussionmentioning
confidence: 99%
“…The NF90-NF45 complex may thus inhibit the processing of pri-miRNA by the DGCR8-Drosha complex. NF90-NF45 also showed a higher binding affinity for pri-let-7a-1 than for pri-miR-21 (33).…”
Section: Introductionmentioning
confidence: 98%